Peran Kantor Urusan Agama (KUA) Kec. Medan Petisah dalam Mewujudkan Keluarga Sakinah - Rabiatul Adawiyah; Hasnah Nasution; M. Ade Ilham; Arifah Zahira; Nashwa Ajri Nazhifa; Sri Yanti; Lukman Hakim Gt (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This study examines the role of the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Medan Petisah District in realizing sakinah families within the community. A sakinah family is one of the main goals of marriage in Islam, characterized by tranquility, affection, and harmony based on faith and devotion to Allah SWT. This study aims to analyze the concept of a sakinah family from an Islamic perspective, as well as the role and forms of family development activities carried out by the KUA of Medan Petisah District. The research employs a qualitative method with a descriptive approach through interviews and documentation involving KUA officials and religious counselors. The findings indicate that the KUA plays an active role through premarital guidance and religious counseling in fostering sakinah families. This study is expected to contribute as an evaluation and provide recommendations to improve the effectiveness of sakinah family development programs.